Penerapan Media Pembelajaran Buku Cerita Bergambar untuk Meningkatkan Kemampuan Membaca Siswa Pada Mata Pelajaran Bahasa Indonesia di Kelas III MI Nawwarul Uyun Nw 2 Tutuk: Implementation of Picture Story Book Learning Media to Improve Students' Reading Skills in Indonesian Language Subjects at MI Nawwarul Uyun NW 2 Tutuk - Husnul Laili (Pendidikan Al-Gafari, 2026)
Basically, the aim of Indonesian language lessons in schools is to educate children to be able to communicate well in Indonesian. This research was conducted with the following objectives: 1) To determine the model of application of picture story book learning media for Indonesian Language Lessons; 2) To determine the increase in students' reading after using picture story book learning media in Indonesian Language Lessons. This type of research is classroom action research whose implementation is divided into 2 cycles. Based on the results of the analysis that have been obtained from the pre-cycle, cycle I and cycle II, it shows an increase and improvement in the learning and teaching process from both students and teachers, in cycle II it shows that the results of student learning activities at the first meeting show activities that are classified as less active before the implementation of the cycle from the observation of daily teacher data as many as 3 students out of 10 students, after the implementation of the second meeting, student learning completeness is also still said to be quite active, while classical learning completeness is as many as 4 students out of 10 students.